Perbedaan Efektivitas Diskusi Kelompok, Motivasi Intrinsik dan Nilai Modul dari Mahasiswa yang Difasilitasi Dosen dan Tutor Sebaya - I Made Pariartha; Rossi Sanusi; Tridjoko Hadianto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: Peer teaching is a teaching method that widely applied in many medical institutions. This research was designed to evaluate group discussion effectiveness, intrinsic motivation, and student achievement differences between peer tutor−facilitated students and faculty tutor−facilitated students.Method: This research is an experimental research using post−test only control group design during the implementation of third and fourth module of the Cardiovascular Block (consist of five modules). Fifty-nine third year students were randomly assigned into two groups. Three experimental groups (n= 30) was facilitated by peer tutors (PT) and three control groups (n= 29) was facilitated by faculty tutors (FT). Two students were randomly elected from each PT group as peer tutor. A six hour training was given to the peer tutors. In the end of the third and fourth module, group discussion effectiveness, intrinsic motivation, and student achievement in those modules were evaluated using Tutorial Group Effectivenes Instrument (TGEI) questionnaire, Intrinsic Motivation Inventory (IMI) questionnaire, and 20 multiple choice questions, respectively. Mean differences between groups were measured by Cohen's d with the practical significance at Cohen's d > 1.Results: There was no significant differences of group discussion effectiveness (Cohen’s d= -0.41) and intrinsic motivation (Cohen’s d= -0.83) between two groups. Significant difference in student achievement is found between those groups, peer tutor−facilitated students score higher than faculty tutor−facilitated students (Cohen’s d= 2.96). Peer tutors showed higher achievement than discussants (Cohen’s d= 1.86).Conclusion: The results showed that peer tutor can facilitated group discussion as well as faculty tutor in group discussion effectiveness, intrinsic motivation and student achievement paramaters. There was advantage for students who given role as peer tutor.